Progress and prospects of nanozymes for enhanced antitumor therapy - Yu, Yulong; Zhao, Weiheng; Yuan, Xianglin; Li, Rui (Frontiers in Chemistry, 2022)
Nanozymes are nanomaterials with mimicked enzymatic activity, whose catalytic activity can be designed by changing their physical parameters and chemical composition. With the development of biomedical and material science, artificially created nanozymes have high biocompatibility and can catalyze specific biochemical reactions under biological conditions, thus playing a vital role in regulating physiological activities. Under pathological conditions, natural enzymes are limited in their catalytic capacity by the varying reaction conditions. In contrast, compared to natural enzymes, nanozymes have advantages such as high stability, simplicity of modification, targeting ability, and versatility. As a result, the novel role of nanozymes in medicine, especially in tumor therapy, is gaining increasing attention. In this review, function and application of various nanozymes in the treatment of cancer are summarized. Future exploration paths of nanozymes in cancer therapies based on new insights arising from recent research are outlined.